Digital Storytelling and Brand Engagement on Social Media - Fauzi, Fahmi; Wardyono, Dion (Jobmark: Journal of Branding and Marketing Communication, 2022)
The storytelling communication technique, which early humans once used, is now being reused as a communication strategy, especially in digital (social) media. Storytelling wants to leave a profound message to trigger the audience's emotional sense, always be remembered, and put in the heart, so that a brand that uses storytelling can make the audience join or be involved in the brand. Skindivore is a brand that uses storytelling in its Instagram social media as an effort to build brand engagement. This study uses an explanatory case study method, which explains a case from the perspective of theory or the concept of brand storytelling and brand engagement with a qualitative approach. The data analysis technique used is an analysis of @skindivore's Instagram content and interviews with several followers of Instagram @skindivore and the owner and content marketing of Skindivore. Findings show that brand storytelling carried out by Skindivore can build brand engagement that is stronger and different from other skincare brands. Brand storytelling Skindivore as an effort to build brand engagement on Instagram has met three criteria for brand storytelling and was able to make brand engagement in front of its followers based on four criteria from Evans.